2023
DOI: 10.1371/journal.pone.0281981
|View full text |Cite
|
Sign up to set email alerts
|

Identification of host genomic biomarkers from multiple transcriptomics datasets for diagnosis and therapies of SARS-CoV-2 infections

Abstract: The pandemic of COVID-19 is a severe threat to human life and the global economy. Despite the success of vaccination efforts in reducing the spread of the virus, the situation remains largely uncontrolled due to the random mutation in the RNA sequence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which demands different variants of effective drugs. Disease-causing gene-mediated proteins are usually used as receptors to explore effective drug molecules. In this study, we analyzed two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 143 publications
0
2
0
Order By: Relevance
“…We considered three methods DESeq2, edgeR and LIMMA (voom) for the identification of DEGs between SARS-CoV-2 infections and control groups separately from RNA-Seq profile datasets [ 23 , 24 ]. To identify DEGs between lung disease and control samples based on microarray gene expression profile datasets, separately we utilized KW, SAM, and LIMMA approaches [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We considered three methods DESeq2, edgeR and LIMMA (voom) for the identification of DEGs between SARS-CoV-2 infections and control groups separately from RNA-Seq profile datasets [ 23 , 24 ]. To identify DEGs between lung disease and control samples based on microarray gene expression profile datasets, separately we utilized KW, SAM, and LIMMA approaches [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The GO functional and pathway enrichment analysis of hub-sDEGs were performed by using ‘Enrichr’ and ‘DAVID’ databases [ 6 , 24 ]. Then, we extracted common GO terms and pathways from both databases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to inhibit microbial pathogens, it is required to identify pathogenic genes that may lead to exploring potential inhibitors. It may be mentioned here that either disease-causing microbial proteins or host-proteins are considered the receptor proteins for exploring candidate drug molecules in order to inhabit microbial infections [ 6 , 9 , 35 , 36 , 37 , 38 , 39 , 40 ], since pathogenic proteins interact with host-proteins to develop infections [ 39 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of COVID-19 research has been devoted to phenotype, proteomic 8, 9 and/or transcriptomic studies 10, 11, 12 , which has given vital information on the dynamics of the immune cell landscape heretofore. In a previous study, we revealed persistent alterations within the monocytic, dendritic cell, and T cell compartments induced by SARS-CoV-2 infection, which manifested even six to seven months post-hospitalization 13, 14 .…”
Section: Introductionmentioning
confidence: 99%